Drying effects on physicochemical and functional properties of cuttlefish (Sepia officinalis) ink powder - Salma Salsabila; Soraya Kerdpiboon; William L. Kerr; Tongchai Puttongsiri (My University, 2024)
This study investigated the physicochemical, functional, and organoleptic properties of cuttlefish (Sepia officinalis) ink powder prepared by freeze drying and hot air tray drying. Key proximate and physicochemical properties were measured to assess differences due to drying method. In addition, organoleptic tests were conducted on cuttlefish ink powder incorporated into spaghetti sauce. Freeze-dried powders had slightly higher moisture (9.86%) than tray-dried powders (7.65%) and more ash (15.04 versus 13.19%). Both samples had ∼43% protein, a light-brown to black color and a pH of 5.5-5.6 when rehydrated. There were no differences in loose or tapped density and Hausner ratios of 1.30-1.35 suggest the powders had 'passable' flow. Overall protein solubility varied with pH and freeze-dried materials generally had greater solubility. FT-IR showed no differences in peaks derived from organic components. FE-SEM showed both samples had spherical granules that formed 100-200 nm clusters; however, the surface texture of tray-dried powders was rougher than the freeze-dried samples. Consumer tests showed higher overall likability for spaghetti sauce with fresh ink compared to dried ink powders. Differences were attributed more to texture than to flavor or appearance. Cuttlefish ink can be utilized in the food industry, particularly as a natural flavor, food coloring or additive.
Keywords: Cuttlefish; Sepia; Tray; Organoleptic; Texture (cosmology); Dried fruit; Cephalopods and Marine Biology